Cross-frequency coupling in deep brain structures upon processing the painful sensory inputs. (10th September 2015) - Liu, C.C.; Chien, J.H.; Kim, J.H.; Chuang, Y.F.; Cheng, D.T.; Anderson, WS; Lenz, F.A.
Highlights: Pain-related gamma responses can be recorded outside sensory cortices. Pain-related gamma responses couple with the low-frequency theta and alpha. Pain-related gamma responses are localized in the right limbic structures. Abstract: Cross-frequency coupling has been shown to be functionally significant in cortical information processing, potentially serving as a mechanism for integrating functionally relevant regions in the brain. In this study, we evaluate the hypothesis that pain-related gamma oscillatory responses are coupled with low-frequency oscillations in the frontal lobe, amygdala and hippocampus, areas known to have roles in pain processing. We delivered painful laser pulses to random locations on the dorsal hand of five patients with uncontrolled epilepsy requiring depth electrode implantation for seizure monitoring. Two blocks of 40 laser stimulations were delivered to each subject and the pain-intensity was controlled at five in a 0–10 scale by adjusting the energy level of the laser pulses. Local-field-potentials (LFPs) were recorded through bilaterally implanted depth electrode contacts to study the oscillatory responses upon processing the painful laser stimulations. Our results show that painful laser stimulations enhanced low-gamma (LH, 40–70 Hz) and high-gamma (HG, 70–110 Hz) oscillatory responses in the amygdala and hippocampal regions on the right hemisphere and these gamma responses were significantly coupled with the phases of theta (4–7 Hz) and alpha (8–12 Hz) rhythms during pain processing. Given the roles of these deep brain structures in emotion, these findings suggest that the oscillatory responses in these regions may play a role in integrating the affective component of pain, which may contribute to our understanding of the mechanisms underlying the affective information processing in humans.